A Decade of Antiretroviral Therapy Scale-up in Mozambique: Evaluation of Outcome Trends and New Models of Service Delivery Among More Than 300, 000 Patients Enrolled During 2004—2013. (1st October 2016) - Auld, Andrew F.; Shiraishi, Ray W.; Couto, Aleny; Mbofana, Francisco; Colborn, Kathryn; Alfredo, Charity; Ellerbrock, Tedd V.; Xavier, Carla; Jobarteh, Kebba
Abstract : Background: During 2004–2013 in Mozambique, 455, 600 HIV-positive adults (≥15 years old) initiated antiretroviral therapy (ART). We evaluated trends in patient characteristics and outcomes during 2004–2013, outcomes of universal treatment for pregnant women (Option B+) implemented since 2013, and effect on outcomes of distributing ART to stable patients through Community ART Support Groups (CASG) since 2010. Methods: Data for 306, 335 adults starting ART during 2004–2013 at 170 ART facilities were analyzed. Mortality and loss to follow-up (LTFU) were estimated using competing risks models. Outcome determinants were estimated using proportional hazards models, including CASG participation as a time-varying covariate. Results: Compared with ART enrollees in 2004, enrollees in 2013 were more commonly female (55% vs. 73%), more commonly pregnant if female (<1% vs. 30%), and had a higher median baseline CD4 count (139 vs. 235/μL). During 2004–2013, observed 6-month mortality declined from 7% to 2% but LTFU increased from 24% to 30%. Pregnant women starting ART with CD4 count >350/μL and WHO stage I/II under Option B+ guidelines in 2013 had low 6-month mortality (0.1%) but high 6-month LTFU (38%). During 2010–2013, 6766 patients joined CASGs. In multivariable analysis, compared with nonparticipation in CASG, CASG participation was associated with 35% lower LTFU but similar mortality. Conclusions: Initiation of ART at earlier disease stages in later calendar years might explain observed declines in mortality. Retention interventions are needed to address trends of increasing LTFU overall and the high LTFU among Option B+ pregnant women specifically. Further expansion of CASG could help reduce LTFU. Abstract : Supplemental Digital Content is Available in the Text.